Journal of communications (Academy Publisher, 2006)
"[Focuses] on theories, systems, methods, algorithms and applications in communications."--Journal home page.
Keywords: Telecommunication : Periodicals; Signal processing : Periodicals; Signal processing; Telecommunication; Telecommunications